The association of COVID-19 vaccine availability with mental health among adults in the United States - Shen, Chan; Rashiwala, Lucy; Wiener, R. Constance; Findley, Patricia A.; Wang, Hao; Sambamoorthi, Usha (Frontiers in Psychiatry, 2022)
Objective To assess whether COVID-19 vaccine approval and availability was associated with reduction in the prevalence of depression and anxiety among adults in the United States. Methods We adopted cross sectional and quasi-experimental design with mental health measurements before vaccine availability (June 2020, N = 68,009) and after vaccine availability (March 2021, N = 63,932) using data from Census Pulse Survey. Depression and anxiety were derived from PHQ-2 and GAD-2 questionnaires. We compared rates of depression and anxiety between June 2020 and March 2021. Unadjusted and adjusted analysis with replicate weights were conducted. Results Depression prevalence was 25.0% in June 2020 and 24.6% in March 2021; anxiety prevalence was 31.7% in June 2020 and 30.0% in March 2021 in the sample. In adjusted analysis, there were no significant differences in likelihood of depression and anxiety between June 2020 and March 2021. Conclusion Depression and anxiety were not significantly different between June 2020 and March 2021, which suggests that the pandemic effect continues to persist even with widespread availability of vaccines.